2010
DOI: 10.1098/rspa.2010.0078
|View full text |Cite
|
Sign up to set email alerts
|

Dropouts of the outer electron radiation belt in response to solar wind stream interfaces: global positioning system observations

Abstract: We present a statistical study of relativistic electron counts in the electron radiation belt across a range of drift shells (L * > 4) combining data from nine combined X-ray dosimeters (CXD) on the global positioning system (GPS) constellation. The response of the electron counts as functions of time, energy and drift shell are examined statistically for 67 solar wind stream interfaces (SIs); two-dimensional superposed epoch analysis is performed with the CXD data. For these epochs we study the radiation belt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
152
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(169 citation statements)
references
References 55 publications
17
152
0
Order By: Relevance
“…Such a boundary can account for the magnetopause shadowing as well as the drift splitting, and the amount of electron loss into the solar wind can be explicitly quantified. This paper primarily focuses on quantifying the relative contribution of magnetopause shadowing in the electron flux dropouts during 67 HSS events (from Morley et al, 2010a) by simulating the magnetopause shadowing effect in the 1-D radial diffusion model. Section 2 describes the GPS data that will be used to obtain the total electron loss during HSS dropout events.…”
Section: Y Yu Et Al: Quantifying the Effect Of Magnetopause Shadowingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a boundary can account for the magnetopause shadowing as well as the drift splitting, and the amount of electron loss into the solar wind can be explicitly quantified. This paper primarily focuses on quantifying the relative contribution of magnetopause shadowing in the electron flux dropouts during 67 HSS events (from Morley et al, 2010a) by simulating the magnetopause shadowing effect in the 1-D radial diffusion model. Section 2 describes the GPS data that will be used to obtain the total electron loss during HSS dropout events.…”
Section: Y Yu Et Al: Quantifying the Effect Of Magnetopause Shadowingmentioning
confidence: 99%
“…In this study, we use the superposed epoch results of interplanetary and geomagnetic parameters from 67 HSS events spanning from year 2005 to 2008 studied by Morley et al (2010a) (Fig. 1).…”
Section: Datamentioning
confidence: 99%
“…Based on some of the earliest observations of outer belt electrons, Dessler and Karplus [1961] presented a theory that explained dropouts as simply an adiabatic effect during the main phase of geomagnetic storms: essentially, as the magnetic field strength in the inner magnetosphere dropped during storm main phase, electron drift shells expanded in physical space to conserve the third adiabatic invariant, Φ or L* [Roederer, 1970], and as the particles moved away from the Earth to regions of lower field strength, they lost energy due to conservation of the first and second adiabatic invariants, μ and K. Since there are exponentially fewer particles at higher energy, this adiabatic motion would be observed as a distinct drop in particle flux. However, it has now been shown that dropouts can also occur independent of geomagnetic storms [e.g., Morley et al, 2010] and that the adiabatic effects alone cannot explain the magnitude of loss observed during dropouts [e.g., Kim and Chan, 1997;Li et al, 1997]. The clearest evidence that outer belt dropouts are driven by true losses from the system (i.e., not just adiabatic effects) have resulted from studies of events, revealing that distributions of electron phase space density (PSD) in adiabatic invariant coordinates, which remove most of the ambiguity due to purely adiabatic effects, also undergo outer belt dropouts [e.g., Turner et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Morley et al [2010] have conducted a superposed epoch analysis to the electron count dropouts associated with 67 CIRs from 2005 to 2008. They found that the dropouts are related to the increased dynamic pressure during these 67 events associated with solar wind stream interfaces.…”
Section: 1002/2015ja021003mentioning
confidence: 99%